2021
DOI: 10.5152/j.aott.2021.20263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 pandemic curfew on orthopedic trauma in a tertiary care hospital in Turkey

Abstract: Objective This study aimed to investigate whether various curfew practices affect trauma prevalence, epidemiological differences among the population admitted to hospital because of trauma, and treatment practices used after trauma. Methods Patients who suffered from fractures or soft-tissue trauma between March 21, 2020, and June 1, 2020, (group pandemic) and during the same period in 2019 (control group) were included in our single-center retrospective study. Each gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…With two research designs being most similar to ours, the study conducted by Kalem et al, investigating the effects of the COVID-19 pandemic curfew on orthopaedic trauma in our country, reported that the number of admissions due to trauma decreased by 50.9% during the pandemic, but the rate of trauma throughout the skeletal system, especially in the upper extremity, was reported to have increased from 30.5% to 49.9% [ 5 ]. The second study similar to ours, conducted by Turgut et al reported that, compared to the pre-pandemic period, the frequency of fractures decreased by about one-third during the pandemic, the average age of the patients with fractures in the paediatric group decreased, and finger fractures in paediatric patients and metatarsal fractures in adult patients decreased significantly during the pandemic [ 13 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…With two research designs being most similar to ours, the study conducted by Kalem et al, investigating the effects of the COVID-19 pandemic curfew on orthopaedic trauma in our country, reported that the number of admissions due to trauma decreased by 50.9% during the pandemic, but the rate of trauma throughout the skeletal system, especially in the upper extremity, was reported to have increased from 30.5% to 49.9% [ 5 ]. The second study similar to ours, conducted by Turgut et al reported that, compared to the pre-pandemic period, the frequency of fractures decreased by about one-third during the pandemic, the average age of the patients with fractures in the paediatric group decreased, and finger fractures in paediatric patients and metatarsal fractures in adult patients decreased significantly during the pandemic [ 13 ].…”
Section: Discussionmentioning
confidence: 88%
“…Research has even shown that mortality rates increased due to myocardial infarction during the pandemic, notably because of refusal to present to the hospital [3,4]. Similar conditions appeared for both elective and emergency cases of orthopaedics and traumatology [5].…”
Section: Introductionmentioning
confidence: 84%
“…Both in Turkey and in other countries, the number of patients who admitted to the hospital after March 2020 was lower than the corresponding periods of the previous year. In studies conducted in tertiary hospitals in Turkey, Kalem et al, found that trauma cases admitted to the orthopedics department of a hospital in Ankara decreased by 50% [7], while Turgut et al, showed that the number of fracture-related applications in Izmir decreased from 1634 to 645 [8]. Significant reductions in trauma cases have been reported during the COVID-19 pandemic in Italy [9], the Republic of Ireland [10], and India [11].…”
Section: Discussionmentioning
confidence: 99%
“…Kalem et al [ 30 ] studied the effect of COVID-19 pandemic on the prevalence and epidemiology in 361 orthopedic trauma patients in Turkey. The study examined the fractures distribution in three age categories (≤ 20 years, 21-64 years, and ≥ 65 years).…”
Section: Clinical Presentationsmentioning
confidence: 99%